Cops and Counselors: How School Staffing Decisions Relate to Exclusionary Discipline Rates and Racial/Ethnic Disparities - Fisher, Benjamin W. (Race and social problems, 2024)
The presence of school-based law enforcement (SBLE) and school counselors is likely to shape how schools punish students. This study examines how schools’ addition or removal of both types of school staff shapes both out-of-school suspension rates and expulsion rates, with a particular focus on differences among white, black, and Hispanic students. It also examines how these relationships differ by school racial composition. Using the 2013–2014 and 2017–2018 waves of the Civil Rights Data Collection, (N = 81,933 schools), this study creates a two-wave panel data set to use a difference-in-differences approach to examine change over time. The results of a series of two-way fixed effects models indicated that changes in the presence of SBLE shaped exclusionary discipline rates—including racial disparities—in multiple, sometimes surprising ways, and that these effects were often strongest in schools with larger proportions of white students. Changes in the presence of school counselors had fewer and less consistent impacts.